Application of Governance in spatial scales - hassan kamran (تحقیقات کاربردی علوم جغرافیایی)
"Governance" is one of the basic concepts that has attracted the attention of geo-political scientists, and there are contradictory views on this concept, which is one of the main and fundamentally important foundations of the science of geopolitics. The rule of law over higher power and superiority imply that no other legal authority is superior to it. Since the study of sovereignty in political geography is very important, therefore, it is necessary to examine its dimensions and spatial levels. Political geography focuses on the study of phenomena, processes and political currents, and emphasizes their geographic and spatial effects. One of the most important studies in political geography is the study of the country. Each country is made up of three elements of "nation, rule and land".. The linking factor of these three elements is "sovereignty". In political theories, they regard the sovereignty of that government and do not attribute it to any government or government agency alone. At the same time, in no political theory, the notion of sovereignty is not absolute, and it is believed that sovereignty must be exercised within the constitutional framework and in accordance with the law. Land is the space of the state, which, with the spatial scope of the territory, determines the sovereignty of the state, and as the physical container, it includes the body of the political organization. The present article seeks to elaborate on the fact that "sovereignty has different dimensions and levels". The present research is of fundamental type and has been done by descriptive-analytical method. Data collection method is library and computer. Also, data analysis is also qualitative.